Determining factors of service priority in the risk classification of patients with chest pain - Segalla, Amanda Vitoria Zorzi [UNESP]; Santos, Bruna Pegorer [UNESP]; Dos Reis, Denise [UNESP]; Meneguin, Silmara [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To verify the determining factors of high priority in the risk classification and the outcomes of the care provided to adult patients with chest pain. Method: Retrospective study, conducted at an emergency referral service of a public hospital in the interior of São Paulo State, analyzing the records of care performed in the risk classification in 181 medical records of patients with the symptom of chest pain, between August and November 2020. Results: Individuals were most males 98 (54.1%), with moderate pain 133 (73.5), high priority for care 135 (74.5%) and who sought the service spontaneously 139 (76.8%). Of those classified as high priority, 47 (34.8%) were referred to the emergency room and, of these, 27 (17.0%) remained hospitalized. Female gender (p=0.0198; OR=0.40; CI=0.189-0.866) was independently associated with high priority of care. Conclusion: Despite the priority classification, few participants were referred to the emergency room and required hospitalization. Female gender was a protective factor in the risk classification as high priority.
Factores determinantes de la prioridad de servicios en la clasificación de riesgo de pacientes con dolor torácico
Fatores determinantes de prioridade de atendimento na classificação de risco a pacientes com dor torácica
Keywords: Chest pain; Emergency medical services; Nursing care; Triage